2021
DOI: 10.1016/j.infpip.2021.100134
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Prescribing Patterns at COVID-19 Dedicated Wards in Bangladesh: Findings from a Single Center Study

Abstract: Background: As evidence is mounting regarding irrational and often unnecessary use of antibiotics during the COVID-19 pandemic a cross-sectional Point Prevalence Survey (PPS) (in accordance with WHO guideline) was conducted across COVID-19 dedicated wards in Dhaka Medical College and Hospital (DMCH). Methodology: Antibiotic usage data were collected from 193 patients at different COVID-19 dedicated wards at DMCH on 11 June 2020. Comparisons in antibiotic usage were made between different groups usin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
46
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(60 citation statements)
references
References 12 publications
9
46
5
Order By: Relevance
“…In addition, concerns with overuse are documented in the current national guidelines (Box 1). This is similar to the high use of antibiotics among adults admitted to hospital with COVID-19 in Bangladesh 70,71 . This is despite clinicians in most of the surveyed hospitals stating they follow the current national guidelines.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…In addition, concerns with overuse are documented in the current national guidelines (Box 1). This is similar to the high use of antibiotics among adults admitted to hospital with COVID-19 in Bangladesh 70,71 . This is despite clinicians in most of the surveyed hospitals stating they follow the current national guidelines.…”
Section: Discussionsupporting
confidence: 70%
“…Having said this, we are aware of the high use of antimicrobials in hospitals including intensive care units in treating patients with COVID-19 despite only a limited number of patients have concomitant fungal or bacterial infections [62][63][64][65][66][67][68][69] . This includes hospitals in Bangladesh 70,71 . As a result, potentially increasing rates of antimicrobial resistance (AMR) with its associated increase in morbidity, mortality and costs 66,[72][73][74][75][76][77] .…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted in the early pandemic period at Wuhan, China reported, all suspected COVID-19 hospitalized cases were treated with empirical antibiotics [ 14 ]. A similar treatment strategy was found in a recent Bangladeshi study where all confirmed COVID-19 patients received one broad-spectrum antibiotic on admission in a tertiary care hospital [ 35 ]. Our study also found a higher number of antibiotic uses among suspected COVID-19 patients.…”
Section: Discussionmentioning
confidence: 70%
“…Moreover, there is a scarcity of data regarding antimicrobial use among hospital admitted suspected COVID-19 patients in Bangladesh. Available studies reported antibiotic use among confirmed COVID-19 patients, suggesting a wide range of antibiotic use during the COVID-19 pandemic [ 35 , 36 ]. Considering the scarcity of antimicrobial data in this overstressing COVID-19 pandemic situation in Bangladesh, we assessed the proportion of antimicrobial use and factors associated with antibiotic use among suspected COVID-19 patients.…”
Section: Introductionmentioning
confidence: 99%
“…These include encouraging regular hand and addressing environmental hygiene, identification and isolation of patients with COVID-19, surveillance and antibiotic stewardship 38 . Antibiotic stewardship programmes are especially important given the extent of inappropriate prescribing of antibiotics for patients with COVID-19 in Bangladesh and wider, with only a small minority of patients actually having bacterial or fungal co-infections [39][40][41][42][43] . This also includes high prescribing rates for antibiotics among children with COVID-19 in hospitals in Bangladesh despite guidelines advocating more prudent use 44,45 .…”
mentioning
confidence: 99%